G Protein-Coupled Receptors in the Mammalian Blood-Brain Barrier - Pluimer, Brock R.; Colt, Mark; Zhao, Zhen (Frontiers in Cellular Neuroscience, 2020)
The mammalian neurovascular unit (NVU) is comprised of neurons, glia and vascular cells. The NVU is the nexus between the cardiovascular and central nervous system (CNS). The central component of the NVU is the blood-brain barrier (BBB) which consists of a monolayer of tightly connected endothelial cells covered by pericytes and further surrounded by astrocytic endfeet. In addition to preventing the diffusion of toxic species into the CNS, the BBB endothelium serves as a dynamic regulatory system facilitating the transport of molecules from the bloodstream to the brain and vis versa. The structural integrity and transport functions of the BBB are maintained, in part, by an orchestra of membrane receptors and transporters including members of the superfamily of G protein-coupled receptors (GPCRs). Here, we provide an overview of GPCRs known to regulate mammalian BBB structure and function and discuss how dysregulation of these pathways plays a role in various neurodegenerative diseases.